Heat Shock Protein 20 Gene Superfamilies in Red Algae: Evolutionary and Functional Diversities - Gao, Tian; Mo, Zhaolan; Tang, Lei; Yu, Xinzi; Du, Guoying; Mao, Yunxiang (Frontiers in Plant Science, 2022)
Heat shock protein 20 (Hsp20) genes play important roles in plant growth, development, and response to environmental stress. However, the Hsp20 gene family has not yet been systematically investigated, and its function in red algae (Rhodophyta) remains poorly understood. Herein, we characterized Hsp20 gene families in red algae by studying gene structure, conserved motifs, phylogenetic relationships, chromosome location, gene duplication, cis-regulatory elements, and expression profiles. In this study, 97 Hsp20 genes were identified using bioinformatic methods and classified into 13 subfamilies based on phylogenetic relationships. Phylogenetic analysis revealed that Hsp20 genes might have a polyphyletic origin and a complex evolutionary pattern. Gene structure analysis revealed that most Hsp20 genes possessed no introns, and all Hsp20 genes contained a conserved α-crystalline domain in the C-terminal region. Conserved motif analysis revealed that Hsp20 genes belonging to the same subfamily shared similar motifs. Gene duplication analysis demonstrated that tandem and segmental duplication events occurred in these gene families. Additionally, these gene families in red algae might have experienced strong purifying selection pressure during evolution, and Hsp20 genes in Pyropia yezoensis, Pyropia haitanensis, and Porphyra umbilicalis were highly evolutionarily conserved. The cis-elements of phytohormone-, light-, stress-responsive, and development-related were identified in the red algal Hsp20 gene promoter sequences. Finally, using Py. yezoensis, as a representative of red algae, the Hsp20 gene expression profile was explored. Based on the RNA-seq data, Py. yezoensis Hsp20 (PyyHsp20) genes were found to be involved in Py. yezoensis responses against abiotic and biotic stresses and exhibited diverse expression patterns. Moreover, PyyHsp20 is involved in Py. yezoensis growth and development and revealed spatial and temporal expression patterns. These results provide comprehensive and valuable information on Hsp20 gene families in red algae and lay a foundation for their functional characterization. In addition, our study provides new insights into the evolution of Hsp20 gene families in red algae and will help understand the adaptability of red algae to diverse environments.